What drives the attainment of goals of ethical education in higher institutions? The perception of professional accountants and accounting educators - Onumah, R.M.; Owusu, G.M.Y. (Journal of Applied Research in Higher Education, 2023)
Purpose This study examines the impact of ethics education interventions (EEI) on attaining ethical education goals in higher institutions. Design/methodology/approach The study utilizes a survey method, with questionnaires distributed to accounting instructors from universities and professional accountants in Ghana. The empirical analysis is based on 417 valid responses, and the hypothesized relationships are tested using ordinary least square (OLS) regression. Findings The results indicate that ethics-related courses (ERC), methods of teaching ethics (MTE) and methods of ethics interventions (MEI) have a positive and significant impact on achieving the objective set for EEI in accounting programs. Research limitations/implications This study provides valuable insights for accounting educators and professional body managers in developing accounting ethics curricula in universities and professional accounting institutions. Originality/value This study involves accounting educators and professionals and applies ethical theories of egoism, deontology and utilitarianism to demonstrate the role of ethical interventions in accounting programs in achieving set objectives from a developing country context.
Research Article
Keywords: ethics education interventions; accounting educators; professional accountants